Methods Of Developing Morphological Competence for Students in 3rd Grade Mother Tongue - F.E.Ibragimova; G.E.Sheraliyeva (Zien Journals, 2022)
This articles devotee to highlighting methods of developing morphological competence in 3rd graders.
Keywords: National Program; DTS; Curriculum; Competence